Assessment of bicycle–car accidents under four different types of collision. (March 2017) - Raslavičius, Laurencas; Bazaras, Liudas; Keršys, Artūras; Lukoševičius, Vaidas; Makaras, Rolandas; Eidukynas, Valdas
Bicycle riders are among the highest risk group in traffic. A cyclist simulation study captured kinematics and injuries to legs, pelvis, neck, and head for one human body size. We analyzed the number of parameters (forces acting on left and right tibia, head injury criterion, neck tensile force, neck shear force, and pelvic acceleration) for each of the four different cases: bicyclist ride out—residential driveway, motorist overtaking—undetected bicyclist, bicyclist left turn—same direction, and bicyclist right turn—opposite direction. The comparison of simulation outcomes for leg injuries with official hospital records has shown a very good correlation in terms of injury severity prediction. This study concludes that if countermeasures to prevent fatal cyclist injury in car impacts were to be concentrated on mitigating head and neck impact to the windscreen of the car, a dominant share of fatal cyclist crashes and severe traumatic head injury cases at collision speeds exceeding 40 km/h could be prevented.